Global Professional Identity in Deterretorialized Spaces: A Case Study of a Critical Dialogue Between Expert and Novice Nonnative English Speaker Teachers - Carmen Helena Guerrero Nieto; Bryan Meadows (Universidad Nacional de Colombia, 2015)
This study analyzes the online, peer-peer dialogue between two groups of nonnative English-speaking teachers who are attending graduate programs in Colombia and the United States. Framed by the theoretical concepts of critical pedagogy and global professional identity, a qualitative analysis of the data shows that their expert vs. novice roles played a significant part in shaping their positions on the four themes that they discussed: the role of English language teaching in the global world, institutional constraints on teachers, whose culture to teach, and linguistic diversity in the classroom. This study highlights the responsibility of teacher education programs to cultivate healthy nonnative English speaker teachers' professional identities given the global complexities that continue to unfold around these teachers.